Medication-Related Osteonecrosis of the Jaw and Low-Level Laser Therapy as Adjuvant Treatment: A Case Report - Torres, Amanda Azevedo; de Freitas, Beatriz Leal; Carneiro, Patrick Parry; de Sousa, André Luca Araujo; Ferraz, Maria Ângela Arêa Leão; Mendes, Jean de Pinho; Costa, André Luiz Ferreira; Pinto, Antonione Santos Bezerra (Journal of Lasers in Medical Sciences, 2020)
Introduction: Medication-related osteonecrosis of the jaw (MRONJ) occurs by the use of a drug that has osteonecrosis as one of its side effects. Case Report: We describe a case of a 48-year-old oncological patient who had brain and bone metastasis due to breast cancer and was medicated with bisphosphonates (BPs). She presented cavities, and after an incorrect exodontia, the lesion evolved into jaw osteonecrosis. Then she did a sequestrectomy and was treated using laser therapy. Radiological and clinical features are also described. Conclusion: In a case like this, we notice how necessary is a complete evaluation of the oncological patient before some procedures and laser therapy as an effective ally in the management.